Analysis of Multicultural Education in Pancasila and Citizenship Education Learning in Schools (Study at SMPN 21 Mataram) - Raudatul Ismi (al-Afkar, Journal For Islamic Studies, 2026)
Indonesia is a nation with diverse cultures, religions, and languages that should be acknowledged and understood by the younger generation. Multicultural education plays a crucial role in resolving conflicts arising from these differences. This study aims to explore the implementation of multicultural education in Civic Education (PPKn) at SMPN 21 Mataram and identify the supporting and inhibiting factors. A qualitative research approach with a descriptive method was employed. Data were collected through interviews, observations, and documentation. The findings indicate that multicultural education is integrated through the school’s vision, mission, curriculum, and inclusive, democratic teaching methods. Key supporting factors include the Merdeka Curriculum, teacher pedagogical competence, and student diversity, while major challenges include low student discipline and limited facilities. In conclusion, the implementation of multicultural education in PPKn at SMPN 21 Mataram has significant potential in developing students who are tolerant and respect diversity, although there are challenges that need to be addressed.